2021
DOI: 10.2147/pgpm.s314860
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dynamics Related Genes -MFN1, MFN2 and DRP1 Polymorphisms are Associated with Risk of Lung Cancer

Abstract: Purpose This study aimed to evaluate the associations between mitochondrial dynamics related genes - MFN1, MFN2 and DRP1 polymorphisms and risk of lung cancer. Methods Six polymorphisms of MFN1, MFN2 and DRP1 were genotyped in 600 cases and 600 controls using a MassARRAY platform. Results The MFN1 rs13098637-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…A recent study identified rs879255685 and rs879255689, resulting in DRP1 missense variants G362D and G379K, in lung cancer patient cells. 98 These mutations were earlier reported to be associated with developmental delay, refractory epilepsy, and altered function of peroxisomes and mitochondria. Among the two, DRP1 rs879255689 was reported to be associated with an increased risk of developing lung cancer.…”
Section: Drp1: Snps and Mutationsmentioning
confidence: 96%
See 3 more Smart Citations
“…A recent study identified rs879255685 and rs879255689, resulting in DRP1 missense variants G362D and G379K, in lung cancer patient cells. 98 These mutations were earlier reported to be associated with developmental delay, refractory epilepsy, and altered function of peroxisomes and mitochondria. Among the two, DRP1 rs879255689 was reported to be associated with an increased risk of developing lung cancer.…”
Section: Drp1: Snps and Mutationsmentioning
confidence: 96%
“…These mutations were earlier reported to be associated with developmental delay, refractory epilepsy, and altered function of peroxisomes and mitochondria. Among the two, DRP1 rs879255689 was reported to be associated with an increased risk of developing lung cancer …”
Section: Crosstalk Between Drp1 and Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have proven that MFN1 and MFN2 are responsible for the fusion and physiological function maintenance of the mitochondria (Liang & Dang, 2021;Yapa et al, 2021). Growing evidences indicate that MFN2 is essential to the maintaining of mammalian follicle development, oocyte maturation, and normal secretion of P4 (Hashem et al, 2020;Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%